Is lumican responsible for the low angiogenetic potential of the adult mammalian heart?. (10th June 2022) - Alfi, E; Kocijan, T; Colliva, A; Abdelaleem, GHA; Shevchuk, O; Vodret, S; Myers, M; Sickmann, A; Zacchigna, S
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): AIRC Introduction: Adult mammals fail to regenerate the myocardium after ischemic injury (1). Different strategies to achieve myocardial regeneration have been considered including reactivation of progenitor cell populations, cell replacement therapies, cell reprograming and molecules able to stimulate cardiomyocyte proliferation (2). None of these approaches has been so far successful. The supply of nutrients and oxygen to the myocardium after the occlusion of a coronary artery depends on pre-existing and newly formed collateral vessels (3). The relevance of revascularization in the context of cardiac regeneration is suggested by the evidence that angiogenesis precedes cardiomyocyte proliferation in a model of neonatal heart injury (4). Our laboratory has recently demonstrated that the heart has a low angiogenetic potential (5). To what extent this is responsible for the poor regenerative capacity of the heart remains to be determined. Thus, understanding the mechanisms blocking angiogenesis in the adult heart could lead to the development of efficient strategies to promote cardiac revascularization and regeneration. Purpose: Our purpose is to understand the mechanisms responsible for the low angiogenic potential of the adult mammalian heart. In particular, we designed a proteomic approach to detect differences in the composition of the perivascular extracellular matrix between the neonatal (angiogenic) with and the adult (not angiogenic) heart. Methods and Results: We adopted an in vivo biotinylation strategy to label vascular extracellular proteins in vivo, followed by protein identification by mass spectrometry. A reactive derivative of biotin was systemically injected in both neonatal and adult mice (n=4) to label vascular and peri-vascular extracellular proteins. Biotinylated proteins were purified from total hearts by streptavidin-conjugated beads, eluted, and digested with trypsin. The resulting peptides were analyzed by LC-MS/MS. Among the differentially expressed proteins, we identified lumican and its receptor, integrin beta-1. This ligand-receptor pair is known to impair tube formation by endothelial cells and to interfere with both expression and activity of matrix metalloproteinases (MMPs) in vitro (6). Western blot and gene expression analysis confirmed up-regulation of lumican in the adult compared to neonatal heart, as well as a different glycosylation pattern. Lumican knock-out both ex vivo and in vivo resulted in increased vessel density. On the other hand, overexpression of lumican impaired the proliferative capacity of cardiac endothelial cells. Finally, MMP-14 activity was inhibited by adult, but not neonatal cardiac extract. Conclusions: In vivo proteomic analysis identified lumican as a major contributor of the low angiogenic potential of the adult mammalian heart. These results point to lumican silencing as a promising strategy to achieve cardiac revascularization.